2008
DOI: 10.1007/s11999-007-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Courses of the Radial Nerve Differ Between Chinese and Caucasians

Abstract: We analyzed anatomic distribution of the radial nerve in the upper arms in Chinese-adult embalmed cadavers (120 nerves in 60 cadavers) and compared it with findings reported for Caucasian adults. The acromion, the medial epicondyle, and the lateral epicondyle were used as bony landmarks. We used previously described techniques to quantitatively describe the location of the radial nerve in relation to the surrounding skeleton. Courses of the radial nerve relative to the humeral shaft in Chinese subjects differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 22 publications
3
26
1
Order By: Relevance
“…Differences in limb length [10] and weight between our group (Caucasian) and Oriental patients were previously recognized [35,36].…”
Section: One Muscle Transfer For Simultaneous Reconstruction Of Two Fsupporting
confidence: 52%
“…Differences in limb length [10] and weight between our group (Caucasian) and Oriental patients were previously recognized [35,36].…”
Section: One Muscle Transfer For Simultaneous Reconstruction Of Two Fsupporting
confidence: 52%
“…Knowledge of the location of the radial nerve during the posterior approach to the humerus, and its relationship with a consistent and reliable anatomic landmark, are major concerns for treating surgeons. Another anatomic landmark is needed to consistently and reliably allow the surgeon to locate the radial nerve during this approach, as described relationships [1,[3][4][5][6][7][12][13][14] of the radial nerve with various osseous landmarks rarely hold true in the clinical setting. Therefore, we compared the distance of the radial nerve from the apex of the triceps aponeurosis among cadavers (having an intact humerus) and patients treated with open reduction and internal fixation for distal third humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
“…First, our subjects were all inhabitants of the Indian subcontinent. The measurements may differ slightly among patients of different race and ethnicity, as Chou et al [6] reported the courses of the radial nerve differ between Chinese and Caucasians subjects. Future studies may evaluate such relationships in patients of other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations